2019
DOI: 10.1167/iovs.18-26270
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 50 and AQP0 are Essential in Maintaining Organization and Integrity of Lens Fibers

Abstract: PurposeConnexins and aquaporins play essential roles in maintaining lens homeostasis and transparency and there is a close physical and functional relationship between these two proteins. Aquaporin 0 (AQP0), in addition to its role in water transport in the lens, acts as a cell–cell adhesion molecule. Recently, we showed a new role of connexin (Cx) 50 in mediating cell–cell adhesion. However, the cooperative roles of these two proteins in the lens in vivo have not been reported.MethodsWe generated an AQP0/Cx50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…This is more evident in the posterior region of the lens, including posterior subcapsular and polar cataracts, and posterior capsular rupture with severe extrusion of lens fiber cells. We also reported disorganized fiber cell structures with abnormally enlarged extracellular spaces ( Gu et al., 2019 ). By using this dKO mouse model, we report a direct mechanism for macrophages in the immune-privileged lens organ during damage repair and fibrosis.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This is more evident in the posterior region of the lens, including posterior subcapsular and polar cataracts, and posterior capsular rupture with severe extrusion of lens fiber cells. We also reported disorganized fiber cell structures with abnormally enlarged extracellular spaces ( Gu et al., 2019 ). By using this dKO mouse model, we report a direct mechanism for macrophages in the immune-privileged lens organ during damage repair and fibrosis.…”
Section: Discussionmentioning
confidence: 83%
“…Our previous studies have shown a significant reduction in the eyeball and lens size in Cx50KO and Cx50/AQP0 dKO mice compared with wild-type (WT) and AQP0KO mice ( Gu et al., 2019 ). Here, we found that the increase in lens mass and diameter of the dKO was delayed during postnatal (P) development, and the growth rate was significantly less than those of WT and single KO, especially compared with WT and AQP0 KO groups ( Figures S1 A and S1 B).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The intracellular loop and C-terminal domains are highly diverse among connexin subtypes [6]. Three connexins present in the lens are Cx43, Cx46, and Cx50, of which Cx46 and Cx50 are predominantly expressed in the lens fiber cells [7]. Epithelial cells predominantly express Cx43 and Cx50, while Cx50 and Cx46 are present in bulk of lens fiber cells.…”
mentioning
confidence: 99%